2022
DOI: 10.3390/cancers14184496
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide Kinase (CERK) Emerges as a Common Therapeutic Target for Triple Positive and Triple Negative Breast Cancer Cells

Abstract: Sphingolipids are key signaling biomolecules that play a distinct role in cell proliferation, migration, invasion, drug resistance, metastasis, and apoptosis. Triple-negative (ER-PR-HER2-) and triple-positive (ER+PR+HER2+) breast cancer (called TNBC and TPBC, respectively) subtypes reveal distinct phenotypic characteristics and responses to therapy. Here, we present the sphingolipid profiles of BT-474 and MDA-MB-231 breast cancer cell lines representing the TPBC and TNBC subtypes. We correlated the level of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Increase in ceramide levels also lead to higher levels of glucosylceramides in TNBC tumors, indicative of increased resistance to chemotherapy, a major challenge in TNBC subtype 41 . Tumor of luminal subtype shows pronounced proliferation phenotype, whereas TNBC subtype exhibits distinctly elevated invasion and metastatic phenotype that justifies higher sphingomyelin level in luminal tumors and a higher S1P level in TNBC subtype 42 . Lower sphingomyelin and C1P levels match high ceramide levels in TNBC tissue supporting “sphingodynamic model” that multiple rheostats exist and balance dysregulated sphingolipids during tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in ceramide levels also lead to higher levels of glucosylceramides in TNBC tumors, indicative of increased resistance to chemotherapy, a major challenge in TNBC subtype 41 . Tumor of luminal subtype shows pronounced proliferation phenotype, whereas TNBC subtype exhibits distinctly elevated invasion and metastatic phenotype that justifies higher sphingomyelin level in luminal tumors and a higher S1P level in TNBC subtype 42 . Lower sphingomyelin and C1P levels match high ceramide levels in TNBC tissue supporting “sphingodynamic model” that multiple rheostats exist and balance dysregulated sphingolipids during tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…The different roles played by CerK in more aggressive metastatic BC cell lines with respect to non-metastatic cell lines have been substantiated in a recent and exhaustive study, reporting a detailed analysis of SL profiles and the transcriptional and translational expressions of corresponding metabolizing enzymes in TPBC BT-474 and TNBC MDA-MB-231 cells: each cell type exhibited a unique SL profile, likely responsible for their unique phenotypic behavior, and common enzymes, including CerK, were dysregulated in both cell lines [61]. However, although CerK can be a potential target to contrast tumor cell proliferation and migration in both cell subtypes, siRNA-or NVP-231-mediated CerK inhibition showed that CerK could play different roles in more aggressive metastatic BC cell lines with respect to non-metastatic cell lines.…”
Section: Other Altered Sphingolipid Metabolism Enzymes Involved In Br...mentioning
confidence: 93%
“…In triple negative breast cancer, the up regulation of CERK is significantly related to its chemoresistance, which may be mediated by the up regulation of Ras/ERK and PI3K/Akt pathways ( 64 ). It is worth noting that CERK has become a common therapeutic target for triple positive and triple negative breast cancer cells ( 65 ). The inhibition of acid ceramidase in CDase family causes mitochondrial dysfunction and oxidative stress in pancreatic cancer cells, thus playing an anti-tumor role ( 66 ).…”
Section: Abnormal Sphingolipid Metabolism and Tumormentioning
confidence: 99%
“…In addition, nanoparticle mediated CERK siRNA delivery and hydrogel mediated continuous delivery of CERK inhibitors to tumor sites can also inhibit tumor progression ( 65 ).…”
Section: Potential Role Of Lipid Metabolism Related Drugs In Tumorsmentioning
confidence: 99%